VARIASI FONOLOGIS PEMAKAIAN BAHASA MELAYU KUTAI DI KABUPATEN KUTAI KARTANEGARA - Wenni Rusbiyantoro Rusbiyantoro (Kantor Bahasa Kalimantan Timur, 2019)
This research aims to decribe phonological variation in Melayu Kutai Language in Kutai Kartanegara Regency. In this research, the researcher uses qualitative-descriptive methods, transcripts the data phonetically, and then classifies and analyses the data as well. It consists of three steps that are the provision of data, data analysis, and presentation of the result. The researcher applies identity methods, that are articulatory phonetic and referential identity methods, followed by a classifying technique to sort out the determinants and all subsequent techniques in the data analysis. This research is conducted in Tenggarong, Kembang Janggut, and Kotabangun. The results shows that variations between phonemes a and |, variations between phonemes i and e, variations between phonemes u and o, variations between phonemes u and O, and variations between phonemes i and E.